2015
DOI: 10.17221/437/2015-pse
|View full text |Cite
|
Sign up to set email alerts
|

Using foliar applications of magnesium and potassium to improve yields and some qualitative parameters of vine grapes (Vitis vinifera L.)

Abstract: Grapevine (Vitis vinifera) is a productive drought stress-adapted plant and one of the most economically important fruit crops (Zörb et al. 2014). Production of quality grapes suitable for winemaking depends on numerous factors (Gerendás and Führs 2013). Moretti (2002) stated that among intrinsic (degree of wood maturation, content of nutritive and nitrogenous compounds) and external factors (temperature, rain distribution, soil parameters) the quality of wine produced is also modulated by fertilization to a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…As it is indicated in the Tables 4 and 5, the contents of some total and also available macro and microelements were considerably different than the monitored factors, it could be reflected also in their mutual relations, because in the scientific literature there are the well-known antagonistic and synergetic relations between the individual elements [Vaněk et al 2013, Zlámalová et al 2015. In our study, we observed significant correlations between the content of available and total elements in soil ( Table 6).…”
Section: Content Of Total and Available Macro And Microelementssupporting
confidence: 53%
“…As it is indicated in the Tables 4 and 5, the contents of some total and also available macro and microelements were considerably different than the monitored factors, it could be reflected also in their mutual relations, because in the scientific literature there are the well-known antagonistic and synergetic relations between the individual elements [Vaněk et al 2013, Zlámalová et al 2015. In our study, we observed significant correlations between the content of available and total elements in soil ( Table 6).…”
Section: Content Of Total and Available Macro And Microelementssupporting
confidence: 53%
“…Potassium is one of the most abundant cations in grapes 35 . Potassium is essential for growth, enzyme activation, photosynthesis, osmotic regulation of grape 36 , also for yield and quality of berries 37,38 . The commercial SUNRED product contains a range of inorganic potassium, which plays key roles in catalyzing enzyme activities involved in anthocyanins biosynthesis of berries.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the authors suggest using the Mg-100 dose, as it allowed to increase the Mg content of the bulbs (up to 1.4-fold, when compared to control), with a contextual increase in crop yield (up to 38%). There is evidence that fertilization of Mg via foliar spray can act to improve crop yield and quality [ 66 , 67 ]. The few studies on Mg biofortification show that both MgSO 4 ·7H 2 O and MgCl 2 are effective in enhancing the element content in vegetables.…”
Section: Agronomic Mineral Biofortificationmentioning
confidence: 99%